The Effect of Work from Home and Work-Life Balance on Turnover Intention Mediated by Job Satisfaction - Korompot, Ema Yuaina; Emilisa, Netania; Sofuah, Siti (Journal of Applied Management Research, 2023)
This study aims to analyze the Effect of Work from Home and Work-Life Balance on Turnover Intention mediated by Job Satiscation in Property Industry employees in South Jakarta. This study used a quantitative method with a total of 201 employees using purposive sampling. Hypothesis testing was carried out using the structural equation model (SEM) method with the help of AMOS software. Based on the results of hypothesis testing, it is known that Work from Home has a positive effect on Job Satisfaction, Work-Life Balance has a negative effect on Job Satisfaction, and Job Satisfaction has a positive effect on Turnover Intention. The conclusion, of the research, is to reduce Turnover Intention for employees, it is necessary to reduce pressure on employees by providing career paths, providing benefits according to performance, and holding holiday activity programs for employees. To improve Work-Life Balance, company employees can arrange working hours and holidays and balance time with family and work.